Fire and climatic extremes shape mammal distributions in a fire‐prone landscape. Issue 11 (24th August 2016) - Hale, Susannah; Nimmo, Dale G.; Cooke, Raylene; Holland, Greg; James, Simon; Stevens, Michael; De Bondi, Natasha; Woods, Rachel; Castle, Michael; Campbell, Kristin; Senior, Katharine; Cassidy, Simon; et al.
Abstract: Aim: Extreme climatic events and large wildfires are predicted to increase as the world's climate warms. Understanding how they shape species' distributions will be critical for conserving biodiversity. We used a 7‐year dataset of mammals collected during and after south‐east Australia's Millennium Drought to assess the roles of fire history, climatic extremes and their interactions in shaping mammal distributions. Location: Grampians National Park, south‐eastern Australia. Methods: We surveyed mammals at 36 sites along a ~50‐year post‐fire chronosequence in each of the 7 years. We modelled ten mammal species in relation to fire history, productivity and recent rainfall. Next, we examined the consistency of species' fire response curves across each of three climatic phases relating to the Millennium Drought. Finally, we identified the optimal distribution of fire ages for small and medium‐sized mammal conservation in each of the three climatic phases. Results: The majority of species were influenced by fire history, and all native species were negatively associated with recently burned vegetation. Seven of ten species responded positively to the end of the Millennium Drought, but six of these declined quickly thereafter. Species' responses to fire history differed depending on the climatic conditions. However, the optimal distribution of fire‐age classes consistently emphasized the importance of older age classes, regardless of climatic phase. This distribution is in stark contrast to the current distribution of fire ages across the study region. Main conclusions: Mammals in the study region face an uncertain future. The negative impact of drought, the short‐lived nature of post‐drought recovery and, now, the possibility of a new drought beginning forewarn of further declines. The stark contrast between the optimal and current fire‐age distributions means that reducing the incidence of further fires is critical to enhance the capacity of native mammal communities to weather an increasingly turbulent climate.